Adverse events and dose modifications of tyrosine kinase inhibitors in chronic myelogenous leukemia - Yoshifuji, Kota; Sasaki, Koji (Frontiers in Oncology, 2022)
The prognosis of chronic myelogenous leukemia (CML-CP) in chronic phase has improved dramatically since the introduction of imatinib. In addition to imatinib, second- and third-generation tyrosine kinase inhibitors (TKIs) and a novel allosteric inhibitor, asciminib, are now available. During long-term TKI therapy, the optimal selection of TKI therapy for individual patients requires the understanding of specific patterns of toxicity profile to minimize chronic toxicity and the risk of adverse events, including pulmonary arterial hypertension, pleural effusion, and cardiovascular events. Given the high efficacy of TKI therapy, dose modification of TKI therapy reduces the risk of toxicities and improves the quality of life during therapy. In this review article, we summarize the characteristics and adverse event profile of each TKI and dose modifications in patients with CML-CP and discuss future perspectives in the treatment of CML-CP.